A Laser Reduced Graphene Oxide Grid Electrode for the Voltammetric Determination of Carbaryl; Molecules; Vol. 26, iss. 16 - Saqib M. Muhammad; Dorozhko E. V. Elena Vladimirovna; Barek J. Jiri; Vyskocil V. Vlastimil; Korotkova E. I. Elena Ivanovna; Shabalina A. V. Anastasiya Valerjevna (2021, 2021)
Title screen